ANALISIS PERBANDINGAN PENILAIAN KINERJA KEUANGAN PERUSAHAAN TERDAFTAR PADA SAHAM SYARIAH DI JAKARTA ISLAMIC INDEX: (Studi Kasus di PT XL Axiata Tbk dan PT Telkom Indonesia Tbk) - Ida Muafikoh; Lely Ana Ferawati Ekaningsih (Universitas KH. Mukhtar Syafaat, 2025)
This study aims to analyze the assessment of the financial performance of PT XL Axiata Tbk and PT Telkom Indonesia Tbk as well as knowing and analyzing the differences in the financial performance of the two companies using liquidity ratios, solvency ratios, and profitability ratios. This type of research is a quantitative, the method used is comparative in nature, which means comparing the levels of liquidity, solvency, and profitability on the financial performance of PT XL Axiata Tbk and PT Telkom Indonesia Tbk. Research Results 1) The assessment of PT XL Axiata Tbk's financial performance seen from the liquidity ratio is not good, while in terms of solvency it is very good, and in terms of profitability is not good. 2) The evaluation of PT Telkom Indonesia Tbk's financial performance is seen from a good liquidity ratio, while from the point of view of solvency it is very good, and in terms of profitability it is quite good. 3) There is a difference in the assessment of the financial performance of PT XL Axiata Tbk and PT Telkom Indonesia Tbk, where PT Telkom Indonesia Tbk is better than PT XL Axiata Tbk. This means that PT Telkom Indonesia Tbk has the ability to pay off short-term obligations and be able to pay off debts that are due on time.